Hinduism and the religious arts - Elgood, Heather, 1950- (Religion and the arts., 2000)
The roots between the Hindu religion and the wider culture are deep and uniquely complex. No study of either ancient or contemporary Indian culture can be undertaken without a clear understanding of Hindu visual arts and their sources in religious belief and practice. Defining what is meant by religion - no such term exists in Sanskrit - and what is understood by Hindu ideals of beauty, Heather Elgood provides the best synthesis and critical study of recent scholarship on the topic. In addition, this book offers critical background information for anyone interested in the social and anthropolo.